2020
DOI: 10.4049/immunohorizons.2000024
|View full text |Cite
|
Sign up to set email alerts
|

A Bioinformatic Approach to Utilize a Patient’s Antibody-Secreting Cells against Staphylococcus aureus to Detect Challenging Musculoskeletal Infections

Abstract: Noninvasive diagnostics for Staphylococcus aureus musculoskeletal infections (MSKI) remain challenging. Abs from newly activated, pathogen-specific plasmablasts in human blood, which emerge during an ongoing infection, can be used for diagnosing and tracking treatment response in diabetic foot infections. Using multianalyte immunoassays on medium enriched for newly synthesized Abs (MENSA) from Ab-secreting cells, we assessed anti-S. aureus IgG responses in 101 MSKI patients (63 culture-confirmed S. aureus, 38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 62 publications
(67 reference statements)
0
19
0
Order By: Relevance
“…While this work has identified the autolysin antigens as potential targets (27,(41)(42)(43), it also identified IsdB as the most immunodominant antigen (17). Our clinical research approach has been focused on elucidating the immune proteome against S. aureus in patients with MSKI and correlating their humoral immunity with their clinical outcome (16,17,(19)(20)(21)(44)(45)(46). While this work also found autolysin antigens to have human vaccine potential, we also found a clear signal that humoral immunity against IsdB is associated with poor clinical outcomes, including amputation and septic death (16,17,20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While this work has identified the autolysin antigens as potential targets (27,(41)(42)(43), it also identified IsdB as the most immunodominant antigen (17). Our clinical research approach has been focused on elucidating the immune proteome against S. aureus in patients with MSKI and correlating their humoral immunity with their clinical outcome (16,17,(19)(20)(21)(44)(45)(46). While this work also found autolysin antigens to have human vaccine potential, we also found a clear signal that humoral immunity against IsdB is associated with poor clinical outcomes, including amputation and septic death (16,17,20).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed high titers of anti-IsdB antibodies in sera and PBMC-cultured medium enriched for newly synthesized anti-S. aureus antibodies (MENSA) from patients with diabetic foot infections undergoing foot salvage therapy (20). Most recently, we assessed MENSA from 101 patients with musculoskeletal infection (MSKI) (63 culture-confirmed S. aureus, 38 S. aureus negative) and 52 healthy controls using machine learning and multivariate receiver operating characteristic curves and found that humoral immunity against IsdB is predictive of active MSKI and MSKI type (21). These MSKI are very challenging to treat, as we found the cure rate of 92 patients with fracture-related infection, 86 patients with prosthetic joint infection, and 49 osteomyelitis to be only 62.1% at 1 year after surgical treatment (22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The manufacturer defined assay sensitivity or Lower Limits of Detection for these cytokines are as follows: IFN-γ = 2.4 pg/mL, CCL20 = 3.4 pg/mL, IL-13 = 3.5 pg/mL, IL-9 = 8.7 pg/mL, IL-21 = 3.3 pg/mL, IL-17E/IL-25 = 0.186 pg/mL, and TNF-α = 1.7 pg/mL. Additionally, using our previously validated Luminex bead-based immunoassay ( 48 50 ), anti- S. aureus human antibody responses in serum were assessed 14 days post-infection in huNSG mice with the following S. aureus antigens: iron-regulated surface determinant proteins (IsdA, IsdB, and IsdH), the staphylococcal complement inhibitor (SCIN), the chemotaxis inhibitory protein from S. aureus (CHIPS), α-hemolysin (Hla), autolysin (Atl) functional domains amidase (Amd) and glucosaminidase (Gmd), and Leukocidin LukSF-PV/PVL (LukS-PV, LukF-PV).…”
Section: Methodsmentioning
confidence: 99%
“…14,15 Our group has established a multiplex antibody-detection-based assay that has shown to specifically detect S. aureus in certain MSKI such as DFI, PJI, and soft tissue infections. 6,[15][16][17] This assay allows us to serologically identify immunoglobulin G (IgG) response to speciesspecific antigens, which ultimately determines if an infection is present. 15,16 An antigen-specific multiplex immunoassay measures IgGs in serum as well as newly synthesized antibodies in enriched media (MENSA) from cultured peripheral blood mononuclear cells (PBMCs) of orthopedic infection patients.…”
Section: Introductionmentioning
confidence: 99%